Olympia, Griechenland. Magna Graecia, Italien. Die Architektur der Schatzhäuser von Olympia und ihre Provenienz aus dem griechischen Westen - Wolf, Markus (e-Forschungsberichte des DAI, 2020)
Since June 2018 the Treasuries of the Archaic and early Classical period at Olympia in Southern Greece were explored. The new study is based on the unpublished works of the Researcher Klaus Herrmann, who died in 2015, with the intention to prepare all the material and informations for a final publication. For this reason a new general plan of all the foundations and new drawings of series of architectural elements not yet recorded as well as computer graphics of the reconstruction of some Treasuries were worked out. An important question is also the provenance of some of these buildings and the connection with the mother cities of the Western Greek colonies in Southern Italy and Albania.